Value of Radiology Modalities in Diagnosing Benign and Malignant Tumours of Breast: An Observational Study - Bafaraj, Saeed M (Journal of Diseases, 2017)
Breast cancer is the most common malignant tumor among women. The objective of this research is to evaluate the specificity, sensitivity, and accuracy of BSGI, DC, and WE-MRI in the diagnosis of breast benign and malignant breast tumors. 228 female patients have participated in this observational research. The age was ranged from 31-68 years (mean age 42.37± 8.14 years) with suspicious breast lesions according to physical and imaging examination (mammography and/or ultrasonography). Moreover, women, who have suspected local regional recurrence after resection of malignant breast tumor and who were suspected to have tumor residual following chemotherapy or radiotherapy were also included. All patients underwent breast specific gamma imaging, DW-MRI, and DCE-MRI examination, and the results of breast MRI were compared with the histopathological results that were used as the standard diagnostic method. In this research, 111 women were found to have breast lesion. All breast lesions were undergone histopathological analysis using needle biopsy and/or excisional biopsy. Also, the results of the pathological analysis were correlated and confirmed with ultrasonography and mammography. The pathologic analysis confirmed that 76 (68.5%) of 111 lesions were benign breast lesions and 35 (31.5 %) of 111 were malignant breast lesions. The results proved that BSGI had the best results for the detection of breast lesions (sensitivity 96.7%, specificity 93.6 % and accuracy 94.8%) as compared with DCE-MRI (sensitivity 92.3%, specificity 85.6% and accuracy 88.2%) and diffusion weighted imaging (sensitivity 94.1%, specificity 88.5% and accuracy 91.4%). The research stated that BSGI is the most appropriate diagnostic tool for breast lesions.